Organochlorine Pesticide Residue Analyses in Some Fruit Samples Collected from Konya City Supermarkets - NAGEHAN UCAN, H.; DURSUN, SUKRU; GUR, KEMAL; AKTUMSEK, ABDURRAHMAN (Asian Journal of Chemistry, 2010)
Food demand increased with increasing population on the world and this demand required usage of fertilizers and pesticides in agriculture. Extremely and uncontrolled usage of pesticide give numbers of problem on vegetation and human health. In this study, the existence of organochlorine pesticide residues have been investigated in 18 types of fruit specimens consumed in Konya, Turkey. The numbers of investigated residues of organochlorine pesticides were 24. The examined fruit specimens for analysis of pesticide residues were apple, pear, black grape, plum, quince, carrot, white grape, persimmon, orange, pomegranate, banana, tangerine, pumpkin, grapefruit, strawberry, kiwi, jarusalem artichoke and medlar. As a result, it was found that, the levels of orghanochlorine pesticides in the all investigated furit specimens were lower than those of the MRL of European Legislations.